Glyoxylate cycle gene ICL1 is essential for the metabolic flexibility and virulence of Candida glabrata - Chew, Shu Yih; Ho, Kok Lian; Cheah, Yoke Kqueen; Ng, Tzu Shan; Sandai, Doblin; Brown, Alistair J. P.; Than, Leslie Thian Lung (Nature Publishing Group, 2019)
The human fungal pathogen Candida glabrata appears to utilise unique stealth, evasion and persistence strategies in subverting the onslaught of host immune response during systemic infection. However, macrophages actively deprive the intracellular fungal pathogen of glucose, and therefore alternative carbon sources probably support the growth and survival of engulfed C. glabrata. The present study aimed to investigate the role of the glyoxylate cycle gene ICL1 in alternative carbon utilisation and its importance for the virulence of C. glabrata. The data showed that disruption of ICL1 rendered C. glabrata unable to utilise acetate, ethanol or oleic acid. In addition, C. glabrata icl1∆ cells displayed significantly reduced biofilm growth in the presence of several alternative carbon sources. It was also found that ICL1 is crucial for the survival of C. glabrata in response to macrophage engulfment. Disruption of ICL1 also conferred a severe attenuation in the virulence of C. glabrata in the mouse model of invasive candidiasis. In conclusion, a functional glyoxylate cycle is essential for C. glabrata to utilise certain alternative carbon sources in vitro and to display full virulence in vivo. This reinforces the view that antifungal drugs that target fungal Icl1 have potential for future therapeutic intervention.